Aetiology, Clinical Presentation, and Outcome of Meningitis in Patients Coinfected with Human Immunodeficiency Virus and Tuberculosis - Smita Bhagwan; Kogieleum Naidoo (AIDS Research and Treatment)
We conducted a retrospective review of confirmed HIV-TB coinfected patients previously enrolled as part of the SAPiT study in Durban, South Africa. Patients with suspected meningitis were included in this case series. From 642 individuals, 14 episodes of meningitis in 10 patients were identified. For 8 patients, this episode of meningitis was the AIDS defining illness, with cryptococcus (9/14 episodes) and tuberculosis (3/14 episodes) as the commonest aetiological agents. The combination of headache and neck stiffness (78.6%) was the most frequent clinical presentation. Relapsing cryptococcal meningitis occurred in 3/7 patients. Mortality was 70% (7/10), with 4 deaths directly due to meningitis. In an HIV TB endemic region we identified cryptococcus followed by tuberculosis as the leading causes of meningitis. We highlight the occurrence of tuberculous meningitis in patients already receiving antituberculous therapy. The development of meningitis heralded poor outcomes, high mortality, and relapsing meningitis despite ART.